A spatial decision-making model of smart transportation and urban planning based on coupling principle and Internet of Things. (September 2022) - Zhu, Wenjian
Abstract: To improve the effect of smart transportation planning in the decision-making process of urban planning space, this paper analyzes the coupling of the smart transportation process. Moreover, this paper analyzes the signal influencing factors of the communication process of smart traffic information based on the Internet of Things, and combines sensor analysis technology to improve the transmission effect of smart traffic signals based on the Internet of Things. Furthermore, this paper proposes a spatial decision-making model of smart transportation and urban planning based on the coupling principle and proposes the establishment and update rules of the road network congestion model, as well as the cluster queuing communication between vehicles. Finally, this paper presents a congestion notification method and a road diversion scheme based on vehicle queues. The experimental study shows that the smart transportation and urban planning spatial decision model based on the coupling principle proposed in this paper has a good effect.